2016
DOI: 10.1111/1462-2920.13461
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin‐mediated suppression of 2‐ketoisovalerate reductase in Beauveria bassiana beauvericin biosynthetic pathway

Abstract: Ketoisovalerate reductase (KIVR, E.C. 1.2.7.7) mediates the specific reduction of 2-ketoisovalerate (2-Kiv) to d-hydroxyisovalerate (d-Hiv), a precursor for beauvericin biosynthesis. Beauvericin, a famous mycotoxin produced by many fungi, is a cyclooligomer depsipeptide, which has insecticidal, antimicrobial, antiviral, and cytotoxic activities. In this report, we demonstrated that Beauveria bassiana 2-ketoisovalerate reductase (BbKIVR) acts as a typical KIVR enzyme in the entomopathogenic fungus B. bassiana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…2, His-BbMetE showed significant CaM-dependent inhibition on in vitro assay of MetE activity, indicating that CaM negatively regulates His-BbMetE activity. Many CaM-binding enzymes are negatively regulated by CaM in eukaryotes (Cyert, 2001;O'Day, 2003;Reddy et al, 2011) Recently, we reported two CaM-binding enzymes (BbPAL and BbKIVR) which are highly regulated by CaM in a negative manner (Kim et al, 2015;2016b). Basically, CaM can have the ability to induce a conformational change in BbMetE structure through direct interaction, and this alteration can directly affect the enzymatic activity of B. bassiana.…”
Section: Cam Negatively Regulates Bbmete Activitymentioning
confidence: 99%
“…2, His-BbMetE showed significant CaM-dependent inhibition on in vitro assay of MetE activity, indicating that CaM negatively regulates His-BbMetE activity. Many CaM-binding enzymes are negatively regulated by CaM in eukaryotes (Cyert, 2001;O'Day, 2003;Reddy et al, 2011) Recently, we reported two CaM-binding enzymes (BbPAL and BbKIVR) which are highly regulated by CaM in a negative manner (Kim et al, 2015;2016b). Basically, CaM can have the ability to induce a conformational change in BbMetE structure through direct interaction, and this alteration can directly affect the enzymatic activity of B. bassiana.…”
Section: Cam Negatively Regulates Bbmete Activitymentioning
confidence: 99%
“…The result was consistent with the HPLC measurement of BEA. A previous report showed BbKIVR activity was suppressed under light and salt stress but not affected by oxidative stress in B. bassiana mycelia via the calmodulin (CaM) signaling pathway [ 62 ]. We found that oxidative stress promotes KIVR activity in C. chanhua mycelia.…”
Section: Discussionmentioning
confidence: 99%
“…The depsipeptides, including BEAs, have a common 2-hydroxycarboxylic acid ingredient-D-2 -hydroxyisovalerate (D-Hiv) that is formed from 2-ketoisovalerate (2-Kiv) by a highly specific chiral reduction reaction catalyzed by 2-ketoisovalerate reductase (KIVR) enzyme [50,52,[67][68][69][70]. KIVR has a significant role in the biosynthesis of BEAs as was clearly understood when BEA production was inhibited in a KIVR knock-out B. bassiana mutant [67].…”
Section: Biosynthesismentioning
confidence: 99%
“…Kiv is formed from pyruvate during the biosynthesis of valine and it is the key intermediate in several metabolic pathways, including pantothenate biosynthesis in fungi, bacteria, and plants. It is also involved in producing phosphopantetheinyl prosthetic groups of acyl or peptidyl carrier proteins and co-enzyme A ( Figure 5) [50,52,67,69,70].…”
Section: Biosynthesismentioning
confidence: 99%